KEANEKARAGAMAN KELAS BIVALVIA DI PANTAI CIBUAYA UJUNG GENTENG - Putri, Anissyah Chaerul; Pertiwi, Meilisha Putri; Awaludin, Muhammad Taufik (LP4MK STKIP PGRI Lubuklinggau, 2023)
Cibuaya Beach is one of the beaches in Ujung Genteng Village that is used as a tourist destination because the beach is still very clean and natural. Cibuaya Beach has large beach sand grains and is dominated by mollusk shell fragments. The intertidal zone is the zone bounded by the tidal line and is the narrowest of the marine zones. The coastal ecosystem of Cibuaya Beach consists of coral reefs, seagrasses, and coastal vegetation. This study aims to determine the diversity of Bivalves in Cibuaya Beach Ujung Genteng. This research was conducted at Cibuaya Beach Ujung Genteng in March-April 2022. Determination of the research location using the belt transect method by purposive sampling at three stations namely rocky sand (station 1), seagrass (station 2), and coral reef (station 3). The results obtained were 148 individuals with 11 Bivalve species comprising six families. The value of the diversity index (H') ranged from 1.58-1.99 classified as medium. The value of the evenness index (E) ranges from 0.83-0.88 classified as high. The dominance index value (D) ranges from 0.18-0.24 which is low. The measurement results of abiotic parameters, namely temperature, pH, salinity, humidity, current speed, and light intensity show good values for marine bivalve life. Therefore, the Cibuaya Beach intertidal ecosystem is suitable for the life of the Bivalve class.